Global perspectives and transdisciplinary opportunities for locust and grasshopper pest management and research - Word Ries, Mira (2024)
Locusts and other migratory grasshoppers are transboundary pests.Monitoring and control, therefore, involve a complex system made upof social, ecological, and technological factors. Researchers and thoseinvolved in active management are calling for more integration betweenthese siloed but often interrelated sectors. In this paper, we bring together38 coauthors from six continents and 34 unique organizations, representingmuch of the social-ecological-technological system (SETS) related tograsshopper and locust management and research around the globe, tointroduce current topics of interest and review recent advancements. Together,the paper explores the relationships, strengths, and weaknesses ofthe organizations responsible for the management of major locust-affectedregions. The authors cover topics spanning humanities, social science,and the history of locust biological research and offer insights and approachesfor the future of collaborative sustainable locust management. These perspectives will help support sustainable locust management,which still faces immense challenges such as fluctuations in funding, focus,isolated agendas, trust, communication, transparency, pesticide use,and environmental and human health standards. Arizona State Universitylaunched the Global Locust Initiative (GLI) in 2018 as a response to someof these challenges. The GLI welcomes individuals with interests in locustsand grasshoppers, transboundary pests, integrated pest management,landscape-level processes, food security, and/or cross-sectoral initiatives